Investigating Highway-incurred Soil and Plant Lead Contamination in Iran - Istanbuly, Mustafa Nour; Amiri, Bahman Jabarian; Hamidian, Amir Hussein (Journal of natural sciences, life and applied sciences, 2019)
In the framework of the classical environmental impact assessment (EIA) of roads, there is a considerable likelihood that the required attention is not paid to the interactions of environmental impacts. These interactions exist among various factors of the peripheral environment of roads. Applying a multi- factor approach in EIA tasks would provide the practitioners of EIA with a more integrated approach. This approach would help them achieve more reliable findings for decision-making. Accordingly, integrating laboratory findings with computer-based techniques such as geo-statistical analysis would provide the EIA practitioners with the spatial concentration of pollutants. It directs them into more reliable decisions by decreasing the extent of uncertainty in the decision-making process. In the present study, our findings showed that the lead concentration in the plants had an inverse relationship (r = -0.524, p<0.05) by moving along the highway from Tehran to Karaj. The lead concentration of soil and that of plants showed an indirect relationship (r = -0.390, p<0.05) at the same direction of movement. Moreover, on latitudinal transects from the edge toward the peripheral area of the highway, the lead concentration in plants was directly related to the lead concentration in the soil (r= 0.600, p<0.05). An inverse relationship (r = -0.400, p<0.05) was also observed between the lead concentration in the soil and the latitudinal distance from the edge of the highway. Overlaying the soil-plant lead concentration map and land use/land cover map indicated that 35.94% of the peripheral environmental settings of the highway is covered by urban areas, which implies a considerable number of inhabitants are exposed to health risks due to transportation in the highway.